Coefficient Estimates for Certain Classes of Bi-Univalent Functions. (29th August 2013) - Jahangiri, Jay M.; Hamidi, Samaneh G.
Abstract : A function analytic in the open unit disk 𝔻 is said to be bi-univalent in 𝔻 if both the function and its inverse map are univalent there. The bi-univalency condition imposed on the functions analytic in 𝔻 makes the behavior of their coefficients unpredictable. Not much is known about the behavior of the higher order coefficients of classes of bi-univalent functions. We use Faber polynomial expansions of bi-univalent functions to obtain estimates for their general coefficients subject to certain gap series as well as providing bounds for early coefficients of such functions.